1994
DOI: 10.1159/000139167
|View full text |Cite
|
Sign up to set email alerts
|

Metoclopramide Does Not Affect Renal Function and Atrial Natriuretic Peptide Release in Response to Acute Saline Loading in Conscious Rats

Abstract: It was previously shown in man that metoclopramide (MCP), a dopamine (DA)-2 receptor blocker, attenuates the natriuresis of water immersion. In the present study, we therefore investigated the effects of MCP on renal function and atrial natriuretic peptide (ANP) release in conscious rats. Under basal conditions MCP did not affect glomerular filtration rate (GFR)(7.4 ± 1.7 ml/min/kg without and 7.8 ± 0.6 ml/min/kg with MCP), urinary fractional excretion of Na (FENa) (0.3 ± 0.1% without and 0.3 ± 0.1%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Precise mechanisms of these two pathways are presently unclear, but saline expansion might have dissected the existence of such contradictory dual pathways. Using conscious rats injected with MCP under isotonic ECFV expansion, Nati et al (1994) reported and discussed a role of DA acting via DA2 receptors on renal Na excretion (7). However, our low dose of DA infusion experiment in saline volume-expanded dogs would be explained by a model in which multiple subtypes of DA and multiple second messengers have effects on Na-linked transporters and Na-pump for the modulation of natriuresis.…”
Section: Discussionmentioning
confidence: 99%
“…Precise mechanisms of these two pathways are presently unclear, but saline expansion might have dissected the existence of such contradictory dual pathways. Using conscious rats injected with MCP under isotonic ECFV expansion, Nati et al (1994) reported and discussed a role of DA acting via DA2 receptors on renal Na excretion (7). However, our low dose of DA infusion experiment in saline volume-expanded dogs would be explained by a model in which multiple subtypes of DA and multiple second messengers have effects on Na-linked transporters and Na-pump for the modulation of natriuresis.…”
Section: Discussionmentioning
confidence: 99%
“…Different physiological factors and systems, such as physical factors, prostaglandins, dopamine and NO, have been also found. [15][16][17] In view of the proposed role of L-Arg in regulating sodium and water excretion, we considered that L-Arg may contribute to the diuretic and natriuretic response during volume expansion. Thus, the present study was undertaken to elucidate the effects of L-Arg on blood pressure and renal function during extracellular fluid volume expansion in rats and to determine whether diuretic treatment with FUR can be optimized by the co-administration of L-Arg in this model.…”
Section: Introductionmentioning
confidence: 99%
“…Although atrial natriuretic factor has been reported to contribute to this phenomenon, it is not the only substance involved in the natriuretic response. Different physiological factors and systems, such as physical factors, prostaglandins, dopamine and NO, have been also found 15–17 …”
Section: Introductionmentioning
confidence: 99%